1986
DOI: 10.1073/pnas.83.8.2758
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in calcium content and biochemical processes in cultured skin fibroblasts from aged and Alzheimer donors.

Abstract: Aging and Alzheimer disease lead to alterations in several biochemical properties of cultured skin fibroblasts. Total bound calcium increases in fibroblasts due to normal aging (+52%) and is elevated even further with Alzheimer disease (+197%). Processes that require mitochondrial function, such as glucose and glutamine oxidation, declined in cells from aged donors (-25%) and decreased even further in Alzheimer disease (-46%). In addition, biosynthetic processes that depend upon mitochondrial function, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(80 citation statements)
references
References 42 publications
4
75
1
Order By: Relevance
“…Stimu lation of the lymphocytes revealed a marked sensitivity of the cells from the Alzheimer patients to temporarily increased intracellular free Ca levels [5]. Results obtained from cultured skin fibroblasts from Alzheimer patients have shown an increased amount of total bound Ca [3] but a decreased level of free Ca [4], It has also been observed that the degree of degrada tion of the anion transport protein (band 3) in erythro cytes as well as the rate of spectrin degradation in cultured fibroblasts (which may be calpain dependent) arc in creased from aged and Alzheimer donors [ 19,20], In the latter study, no differences were found in the total activi ties of calpains or calpastatin. These results may possibly be a consequence of a Ca-induced binding of calpains to the cell membranes from Alzheimer patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Stimu lation of the lymphocytes revealed a marked sensitivity of the cells from the Alzheimer patients to temporarily increased intracellular free Ca levels [5]. Results obtained from cultured skin fibroblasts from Alzheimer patients have shown an increased amount of total bound Ca [3] but a decreased level of free Ca [4], It has also been observed that the degree of degrada tion of the anion transport protein (band 3) in erythro cytes as well as the rate of spectrin degradation in cultured fibroblasts (which may be calpain dependent) arc in creased from aged and Alzheimer donors [ 19,20], In the latter study, no differences were found in the total activi ties of calpains or calpastatin. These results may possibly be a consequence of a Ca-induced binding of calpains to the cell membranes from Alzheimer patients.…”
Section: Discussionmentioning
confidence: 95%
“…Aging and Alzheimer's disease arc correlated with changes in Ca homeostasis in different non-neuronal cells [2][3][4][5] as well as in hippocampal neu rons [6], An unregulated level of free Ca in the cytosol may induce changes in Ca-dependent proteolytic systems in neuronal as well as non-neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet complex activity was found to be significantly lower in PD patients than in controls [7, 8]. Similarly, AD patients have shown complex IV abnormalities in platelets [9]as well as abnormalities in the mitochondrial respiratory-chain complex in the neocortex [10]and fibroblasts [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Although AD was first thought to be a disease characterized by a brain-limited amyloidosis (Ogomori et al 1989, Scudiero et al 1986, Peterson and Goldman 1986, Zubenko et al 1987), Joachim and others (1989) have lately reported the detection of amyloid B-protein (G1enner and Wong 1984a) or A4 (Masters et al 1985a) deposits in non-neuronal tissues of AD patients including skin, subcutaneous tissue and intestine. Thus, amyloidosis in AD is systemic in nature.…”
Section: Extracellular Amyloid Ln Alzheimer's Diseasementioning
confidence: 99%